Prospects for India's cereal supply and demand to 2020 - Bhalla, G. S.; Hazell, Peter B. R.; Kerr, John M. (International Food Policy Research Institute, 1999)
The possibility of an emerging cereal gap of serious proportions by the year 2020, is a useful illustration of the kind of constructive dialogue IFPRI hopes to encourage. It responds to several quite recent developments, notably the rapid expansion of India’s industrial and service sectors since the 1991 structural reforms, the improved prospects for continued growth over the next few decades, and the likelihood of rising per capita incomes that could generate substantially increased demand for livestock products. As demand for livestock products grows, livestock production could increasingly depend on cereals for feed — perhaps as much as 50 million tons by 2020, according to G.S. Bhalla, Peter Hazell, and John Kerr, authors of this 2020 discussion paper on Prospects for Balancing Cereal Needs in India to 2020. These conclusions differ somewhat from other IFPRI studies, which have generally found that growth in demand for livestock products will be lower than the current study. This divergence of views is a useful signal to policymakers to pay careful attention to trends in demand for livestock products in India in the coming years. This study and the rest of IFPRI’s 2020 research have consistently pointed to the vital link between agricultural policies and prospects for production growth in the next two decades. (from Forward by Per Pinstrup-Andersen)